Golf injuries and rehabilitation - Parziale, J. R.; Mallon, W. J. (Physical Medicine & Rehabilitation Clinics of North America, 2006)
There are more than 25 million golfers in the united States, and many have an injury related to golf. Low back injuries are the most common golf injuries, followed by elbow injuries. Successful treatment of golf injuries often includes modification of the golf swing. Adaptations allow many individuals, including those who are physically challenged, to enjoy playing golf.